Comportamiento juvenil de nueve procedencias de Pinus caribaea var. hondurensis Barret y Golfari en Costa Rica - Salazar, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This is a preliminary assessment of the provenance test of Pinus caribaea vat. hondurensis Barret and Golfari established by the Tropical Agriculture Research Training Center (CATIE) in Costa Rica. The analysis of the growth at two years of age revealed significant differences among the nine provenances tested. However the genetic variance was never higher than 6.4 percent for the traits assessed. In the provenances Melinda, Guanaja, and Limones, slower growth was observed. This observation was supported by the principal component and cluster analysis, which grouped these three populations separately from the rest. It was found that most of the variables studied showed highly significant differences among the three sites tested. In this juvenile stage, most of the variation was detected between trees within provenances. It will be interesting to follow up these observations to determine if this pattern is maintained in coming years.